Validation of the Bangla version of the Communication Skills Attitude Scale with the medical students of Bangladesh - Mohammad Aminul Islam; Maskura Benzir; Md. Kaoser Bin Siddique; Md. Abdul Awal; Mohiuddin Ahsanul Kabir Chowdhury; Taufique Joarder (Health Science Reports)
Abstract Background Effective communication skill of physicians is an important component of high‐quality healthcare delivery and safe patient care. Communication is embedded in the social and cultural contexts where it takes place. An understanding of medical students' attitudes and learning communication skills would help to design and deliver culturally appropriate medical education. The Communication Skills Attitude Scale (CSAS) is a widely used and validated tool to measure the attitude of medical students toward learning communication skills in different populations, settings, and countries. However, there is no culturally adapted and validated scale in Bangla in the Bangladesh context. This study aims to culturally adapt the CSAS into Bangla, and validate it in a cohort of medical students in Bangladesh. Methods This study used a cross‐sectional survey design to collect data from purposively selected 566 undergraduate medical students from the Rajshahi division. The survey was conducted from January to December 2023. Descriptive statistics like frequency distribution and measures of central tendency were used to measure perception regarding communication skills. The sample adequacy was measured through the Kaiser–Meyer–Olkin test. The internal consistency of the items was identified using Cronbach's alpha (α) coefficients. Result The results of the study show that the Bangla version of the scale is feasible, valid, and internally consistent in the context of a developing country, Bangladesh. The overall internal consistency of the Bangla version is good since the value of Cronbach's alpha (α) is 0.882. For PAS, the internal consistency is 0.933. While, for NAS, the value is 0.719. The item‐wise average scores in the PAS indicate that female medical students are more willing to learn communication skills compared with male students (α = 0.933). While, the scores in the NAS indicate that the male students tend to have more negative attitude toward learning communication skills compared with female students (α = 0.719). Conclusion The CSAS‐Bangla is a valid and reliable tool for assessing communication skill attitudes among Bangla speaking medical students. This scale can be used in future studies to measure the attitude of students, designing and evaluating communication skills training programs in medical colleges.